La historia de la humanidad interpretada de manera humanista - Borrelli, Michelle (Universidad Pedagógica y Tecnológica de Colombia, 2020)
This writing starts from the distancing of idealistic and materialistic readings of the history of humanity, to propose as a first thesis that this history must be interpreted in a humanistic way. In this context, an analysis of two types of humanism is carried out: Greek humanism or of belonging, and modern humanism or of emancipation. The first deals with man’s belonging to the polis, the cosmos, and the regulatory framework of what is considered good, beautiful, and true, for example. The second highlights the values of autonomy, self-determination and freedom of the individual, which slowly fell under the dominion of the market in a subjectivist and selfish individualism, which prevents the harmonious linking of belonging and emancipation. One speaks then of a humanism of technical predominance characterized by profit and money. This new approach marks the rupture of what constitutes the second thesis of this writing: emancipation and belonging are integrated into a humanism of planetary responsibility, which is configured as a countercurrent to contemporary nihilism (third and final thesis).